Polyandry and Polygyny in a Social Rodent: An Integrative Perspective Based on Social Organization, Copulations, and Genetics - Hoogland, John L.; Trott, Regina; Keller, Stephen R. (Frontiers in Ecology and Evolution, 2019)
Animal mating systems have fascinated biologists for thousands of years. Ways to describe a mating system include determining social organization, observing copulations, or using genetics to assign parentage. Social organization can be difficult to quantify, however, documentation of copulations is often challenging, many copulations do not produce offspring, and genetic variation is sometimes minimal. Here we use data from a 7-year study of wild white-tailed prairie dogs (WTPDs, Cynomys leucurus) living in Colorado USA to estimate the frequencies of polyandry (i.e., copulation with ≥2 males) and polygyny (i.e., copulation with ≥2 females) from three independent approaches: (1) determination of the number of males and females living in the same territory (social organization); (2) observations of copulations; and (3) genetic assignments of paternity from seven polymorphic microsatellites. We predicted that our three approaches would yield similar estimates of polyandry and polygyny. Because a WTPD female's period of sexual receptivity each spring is limited to several hours on a single day, we also predicted that frequencies of polyandry and polygyny would be lower for WTPDs than for animals with longer periods of receptivity. Our results did not support these predictions. For polyandry, observations of copulations and genetics indicated similar overall percentages (27%), but social organization indicated a much lower percentage (3%). For polygyny, observations of copulations indicated the highest overall percentage (84%), then social organization (59%), then genetics (46%). All three approaches showed striking annual variation in the frequencies of WTPD polyandry and polygyny. Long-term studies that integrate behavioral and genetic insights can provide a detailed view of a mating system, but feasibility will depend on ease of capture, visibility of copulations, length of mating season, research objectives, and genetic variation.